Book review “Nociones fundamentales sobre sistemas de información empresarial. Teoría y practica” by Hernández y Zapata (Publicaciones en Ciencias y Tecnología, 2015)
The book "Fundamentals of Business Information Systems" presented by Hernández and Zapata authors exposes from a management standpoint, the value of the use of information systems for the generation of competitive advantages in organizations. Divided into three (3) extensive chapters, addressing key issues such as the alignment of ICT projects with business strategy, development of projects and audit IT. Easy to read, recommended for undergraduate and graduate students in the areas of Administration, Management and Information Technology.
Keywords: information systems; business development; IT projects; IT audit